Sigmoid Sinus Patency following Vestibular Schwannoma Resection via Retrosigmoid versus Translabyrinthine Approach - Ziegler, Andrea; El-Kouri, Nadeem; Dymon, Zaneta; Serrano, David; Bashir, Mariah; Anderson, Douglas; Leonetti, John (Journal of Neurological Surgery Part B: Skull Base, 2020)
Introduction The treatment options for acoustic neuromas are observation with serial imaging, stereotactic radiation, or surgical resection. The most common surgical approaches are the translabyrinthine (TL), the retrosigmoid (RS), and the middle cranial fossa. During the TL approach the sigmoid sinus is decompressed with bipolar cautery to allow greater medial exposure. It is unknown if this causes any long-term narrowing or thrombus of the sigmoid sinus.Methods We performed a retrospective review of patients who underwent acoustic neuroma resection to determine if patients undergoing a TL approach for acoustic neuroma resection develop radiographic evidence of sigmoid sinus stenosis or thrombosis compared with patients undergoing a RS approach.Results A total of 128 patients were included in this study, 56 patients underwent a TL approach and 72 patients underwent a RS approach. We compared the preoperative and postoperative diameter of the ipsilateral and contralateral sigmoid sinus at proximal, midpoint, and distal locations on magnetic resonance imaging examinations. There was no significant difference between the preoperative and postoperative diameter of the ipsilateral or contralateral sigmoid sinus based on surgical approach.Conclusion Decompression of the sigmoid sinus during the TL approach does not have a significant postoperative effect on the dural venous sinus patency.
Keywords: acoustic neuroma; vestibular schwannoma; resection approach; sigmoid sinus; dural venous sinus